Research Progress on Regenerative Technology and Energy Analysis of Solar Liquid Desiccant Air-conditioning System - Zhou Junming; Zhang Xiaosong; Sun Bo (Zhileng xuebao, 2019)
Solar liquid desiccant air-conditioning represents a new, environmentally friendly, and energy-saving air-conditioning system. Solar-energy solution regeneration is one of the most important aspects of the system. In this study, a comprehensive review of the latest regeneration technologies for solar liquid desiccant air-conditioning systems is presented. The following three regeneration methods were simulated and compared: photothermal, photovoltaic, and PV/T. The results showed that under ideal conditions, the PV/T-ED regeneration was 40.5% greater than PV-ED regeneration in terms of energy-saving, whereas PV-ED regeneration was 51.6% better than PT regeneration. When the PV/T-ED regeneration was operated for LiCl-H2O, LiBr-H2O, and CaCl2-H2O under ideal conditions, it was found that the LiBr-H2O had the largest concentration difference between the inlet and outlet, whereas the LiCl-H2O had the strongest dehumidification capability after regeneration.